Narrative Review of Emergency Medicine Clinical Research Examining Exclusion by Language. - Curt, Alexa M.; Kahn-Boesel, Olivia; Lydston, Melis; Meeker, Melissa A.; Samuels-Kalow, Margaret E. (Western Journal of Emergency Medicine: Integrating Emergency Care with Population Health, 2025)
Introduction: Over 20% of the United States population speaks a language other than English, and many use the emergency department (ED) to access healthcare. However, there remains concern that patients preferring languages other than English are under-represented in clinical research. Thus, our goal was to assess the proportion of ED studies that excluded patients for recruitment due to language. Methods: We conducted a narrative review using seven search engines for 2018-2023. We included studies if they mentioned language of participants and prospectively enrolled patients in an ED or prehospital setting. We excluded studies if they only included patients <18 years and/or were conducted exclusively outside the US. Two independent reviewers reviewed studies. Analyses included descriptive statistics. Results: Of the 10,513 studies we identified, 281 were eligible for review; 163 (58%) excluded non-English language preferred (NELP) patients. Among the 107 interventional studies, 69% excluded NELP patients. Of the 135 studies focused on health equity/social emergency medicine, 47% excluded NELP patients. Conclusion: We found 163 (58%) studies conducted in the ED that mention language and excluded NELP patients. Additional work is needed to encourage and support inclusive study designs.